Challenges Facing Corporate Communication in Public Universities in Kenya - Munyi, Jessee .; Peter, Christine A. (iosrjournals, 2021)
In the management world today, it’s widely accepted that the future of any organization critically depends on how it is viewed by key stakeholders. Several research studies have shown that corporate communication when effectively used can help organizations acquire goodwill to operate among their stakeholders. The bulk of these studies, however have been conducted in business organizations, government ministries and parastatals. There have been few studies investigating the effectiveness of corporate communication in academic institutions yet the phenomenon of lack of the goodwill granted by stakeholders. The study sought to investigate the challenges facing corporate communication as a management tool in public Universities in Kenya. The study was guided by the Legitimacy theory, Stakeholder theory and the Stakeholder Salience Model. The scope of the study was four public universities in Kenya. The target population for the study was 2040 administrative staff working in public universities in Kenya where a sample size of 334 administrative staff was used. The objective of the study was to: explore the challenges facing corporate communication as a management tool in Public Universities. The study adopted a descriptive research design. Primary data was collected through use of semistructured questionnaires. Additionally, interview guides were used to get insights from students and external publics. Quantitative data was analyzed using descriptive statistics while qualitative data was analyzed using content analysis which involved identification and classifying findings based on themes. The study found that a number of challenges were hindering corporate communication including. failure by Universities to measure communication for both internal and external stakeholders, failure by Universities to take into account contribution of communication practitioners in governance decisions, lack of involvement of stakeholders when implementing organizational change and lack of inducting new employees on communication skills, Universities have not put in place stakeholder communication strategies and communication policies, communication offices are under-funded making execution of communication plans a major challenge and most Universities are yet to fully embrace social media platforms by collecting statistics on their utilization in order to inform decision making. Furthermore, social media policies have not been formulated and implemented in most Universities.